Topological guiding of elastic waves in phononic metamaterials based on 2D pentamode structures. Issue 1 (December 2017) - Guo, Yuning; Dekorsy, Thomas; Hettich, Mike
Abstract A topological state with protected propagation of elastic waves is achieved by appropriately engineering a phononic metamaterial based on 2D pentamode structures in silicon. Gapless edge states in the designed structure, which are characterized by pseudospin-dependent transport, provide backscattering-immune propagation of the elastic wave along bend paths. The role of the states responsible for forward and backward transfer can be interchanged by design.